Maintenance works of air conditioning at Faculty of Office Management (FPP) Universiti Teknologi MARA (Perak) / Muhammad Khairulazman Khadzali - Khadzali, Muhammad Khairulazman (Universiti Teknologi MARA, Perak, 2013)
Maintenance should be considered as an integral part of the project during all phases of the design and preferably during the preparation of the brief. The management of building services maintenance, the reason for such maintenance and its implementation need to be clearly defined. The main contractor should provide the following information: Records drawings showing locations and depths of all external services installed by all contractors and public utilities Details and locations of all access manholes, valves, etc. for the services Details of all tests carried out on external service mains and all statutory approval. The services sub-contractor should provide the following record information: Specially prepared drawings for all piped and wired services, showing all the services installed will full annotations. Updated ductwork, wiring and control panel drawings showing the work as fitted. Updated schedules of all equipment installed, with full means of identifications by site label numbers, component serial number , test certificates, dated installed etc. This Academic building blocks using split unit air-conditioning system Split unit is a separate air conditioning system units evaporation and condensation. The unit is divided into two parts, units and outdoor units. Unit consists of the evaporator and evaporator fan. The outdoor unit consists of a condenser, piping, condenser fan and other add-ons installed locally. Both inside and outside the unit installed separately.